Competitive removal of Cd(ii) and Pb(ii) by biochars produced from water hyacinths: performance and mechanism. Issue 7 (12th January 2016) - Ding, Yang; Liu, Yunguo; Liu, Shaobo; Li, Zhongwu; Tan, Xiaofei; Huang, Xixian; Zeng, Guangming; Zhou, Yaoyu; Zheng, Bohong; Cai, Xiaoxi
Abstract : Three biochars converted from water hyacinth biomass at 300, 450, and 600 °C were used to investigate the adsorption properties of Cd 2+ and Pb 2+ . Abstract : Three biochars converted from water hyacinth biomass at 300, 450, and 600 °C were used to investigate the adsorption properties of Cd 2+ and Pb 2+ . In addition, the competitive adsorption mechanisms between Cd 2+ and Pb 2+ were also conducted. Adsorption kinetics and isotherms indicated that the maximum adsorption capacity of Pb 2+ was larger than that of Cd 2+, and the adsorption process in the mixed solutions of two heavy metals (Cd 2+ and Pb 2+ ) was more favorable for Pb 2+ . Further investigation about the characterization of biochars demonstrated that cation exchange, surface complexation, cation–π interaction and precipitation were the main mechanisms responsible for the heavy metal removal. In this study, competitive adsorption may also be explained by these mechanisms. These results are useful for the application of biochars in selective adsorption and in practical wastewater treatment.